Analysis of Factors Related to Nursing Student Self Wareness in Doing Screening for Psychosocial Problems - Verantika Setya Putri; Ah Yusuf; Rr Dian Tristiana (Jurnal Ners, 2020)
Introduction: Mental health knowledge is a substantial part of mental health literacy. Many psychosocial problems are transient and are often not noticed. This study aimed to analyze the factors related to student self-awareness in conducting psychosocial screening.Methods: This study used a descriptive-analytic design with cross-sectional approach. The study was conducted at the Faculty of Nursing, Universitas Airlangga Surabaya. A total of 160 respondents was chosen using simple random sampling techniques. The instrument used was a questionnaire. The dependent variable in this study was students’ awareness in conducting psychosocial problems screening. The independent variables in this study were knowledge, social interaction, family support, perceived vulnerability, perceived severity, perceived benefits, perceived barriers, and self-confidence. Analysis used multiple linear regression statistical tests.Results: The results showed there was a relationship between social interaction (p=0.00), perceived vulnerability (p=0.00), perceived benefits (p=0.001) and self-confidence (p=0,000) with students’ self-awareness in conducting psychosocial screening. There was no relationship between knowledge (p=0.555), family support (p=0.720), perceived severity (p=0.070), perceived barriers (p=0.748) with students’ self-awareness in conducting psychosocial screening.Conclusion:Mental health awareness in nursing student should be enhanced and strengthened with health education. Self-awareness of mental health is important for students. This can prevent mental disorders in the future